Dramatic Disgust: Aesthetic Theory and Practice from Sophocles to Sarah Kane - Ablett, Sarah J. (transcript, 2020)
Aesthetic disgust is a key component of most classic works of drama because it has much more potential than to simply shock the audience. This first extensive study on dramatic disgust places this sensation among pity and fear as one of the core emotions that can achieve katharsis in drama. The book sets out in antiquity and traces the history of dramatic disgust through Kant, Freud, and Kristeva to Sarah Kane's in-yer-face theatre. It establishes a framework to analyze forms and functions of disgust in drama by investigating its different cognates (miasma, abjection, etc.). Providing a concise argument against critics who have discredited aesthetic disgust as juvenile attention-grabbing, Sarah J. Ablett explains how this repulsive emotion allows theatre to dig deeper into what it means to be human.